Refining trophic dynamics through multi-factor Bayesian mixing models: A case study of subterranean beetles - Sacco, Mattia; Blyth, Alison; Humphreys, W.F.; Cooper, S.J.B.; Austin, A.D.; Hyde, J.; Mazumder, D.; Hua, Q.; White, Nicole; Grice, Kliti (WILEY, 2020)
© 2020 The Authors.